Lipid profile associated with coronary plaque regression in patients with acute coronary syndrome: Subanalysis of PRECISE-IVUS trial. (August 2016) - Tsujita, Kenichi; Yamanaga, Kenshi; Komura, Naohiro; Sakamoto, Kenji; Sugiyama, Seigo; Sumida, Hitoshi; Shimomura, Hideki; Yamashita, Takuro; Oka, Hideki; Nakao, Koichi; Nakamura, Sunao; Ishihara, Masaharu; et al.
Abstract: Background and aims: Although dual low-density lipoprotein cholesterol (LDL-C)-lowering therapy (DLLT) with statin-ezetimibe combination showed clinical benefit in patients with acute coronary syndrome (ACS) confirming "the lower, the better, " the underlying mechanisms of DLLT are still unknown. Methods: PRECISE-IVUS trial evaluated the effects of DLLT on IVUS-derived coronary atherosclerosis and lipid profile, compared with atorvastatin monotherapy, quantifying the coronary plaque response in 100 ACS patients. We explored the potential predictors of plaque regression. Results: Lower total cholesterol, LDL-C, triglyceride, remnant-like particles cholesterol, and stronger reduction of small dense LDL-C and cholesterol absorption markers were observed in patients with plaque regression compared to those with progression. Multivariate analysis revealed that achieved LDL-C was the strongest predictor for coronary plaque regression (95% CI: 0.944–1.000, p = 0.05), followed by age (95% CI: 0.994–1.096, p = 0.09). Conclusions: Incremental LDL-C lowering by DLLT was associated with stronger coronary plaque regression, reconfirming that lowering LDL-C to levels below previous targets provided additional clinical benefit.